More Choice for Men? Marriage Patterns after World War II in Italy - Erich Battistin; Sascha O. Becker; Luca Nunziata (Institute of Labor Economics (IZA), 2020)
We investigate how changes in the sex ratio induced by World War II affected the bargaining patterns of Italian men in the marriage market after the war. Marriage data from the first wave of the Italian Household Longitudinal Survey (1997) are matched with newly digitized information on war casualties coming from Italian National Bureau of Statistics. We find that men in postwar marriages were better off in terms of their spouse's education, this gain amounting to about half a year of education. By considering heterogeneity across provinces, we find that the effects were more pronounced in more rural provinces, mountainous provinces, and those with a higher share of population employed in agriculture. This suggests that here, the shock provided for a more fundamental change in marriage patterns compared to urban, lower-lying, and less agricultural provinces where marriage markets might have been more flexible to begin with.
Keywords: J12; N34; 330; education; marriage; sex ratio; World War II